NagZ Inactivation Prevents and Reverts β-Lactam Resistance, Driven by AmpD and PBP 4 Mutations, in Pseudomonas aeruginosa - Zamorano, Laura (American Society for Microbiology (ASM), 2010)
AmpC hyperproduction is the most frequent mechanism of resistance to penicillins and cephalosporins in Pseudomonas aeruginosa and is driven by ampD mutations or the recently described inactivation of dacB, which encodes the nonessential penicillin-binding protein (PBP) PBP 4. Recent work showed that nagZ inactivation attenuates β-lactam resistance in ampD mutants. Here we explored whether the same could be true for the dacB mutants with dacB mutations alone or in combination with ampD mutations. The inactivation of nagZ restored the wild-type β-lactam MICs and ampC expression of PAO1 dacB and ampD mutants and dramatically reduced the MICs (for example, the MIC for ceftazidime dropped from 96 to 4 μg/ml) and the level of ampC expression (from ca. 1,000-fold to ca. 50-fold higher than that for PAO1) in the dacB-ampD double mutant. On the other hand, nagZ inactivation had little effect on the inducibility of AmpC. The NagZ inhibitor O-(2-acetamido-2-deoxy-d-glucopyranosylidene)amino-N-phenylcarbamate attenuated the β-lactam resistance of the AmpC-hyperproducing strains, showing a greater effect on the dacB mutant (reducing the ceftazidime MICs from 24 to 6 μg/ml) than the ampD mutant (reducing the MICs from 8 to 4 μg/ml). Additionally, nagZ inactivation in the dacB mutant blocked the overexpression of creD (blrD), which is a marker of the activation of the CreBC (BlrAB) regulator involved in the resistance phenotype. Finally, through population analysis, we show that the inactivation of nagZ dramatically reduces the capacity of P. aeruginosa to develop ceftazidime resistance, since spontaneous mutants were not obtained at concentrations ≥8 μg/ml (the susceptibility breakpoint) for the nagZ mutant but were obtained with wild-type PAO1. Therefore, NagZ is envisaged to be a candidate target for preventing and reverting β-lactam resistance in P. aeruginosa.